PERANCANGAN SISTEM PENYIMPANAN REKAM MEDIS TERKOMPUTERISASI MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI RUMAH SAKIT UMUM JAMPANG KULON - Nita Nurazizah Nita Nurazizah (Jurnal Medika Hutama, 2021)
Storage system is an activity to store medical records which aims to protect it from physical damage and the contents of the document. This study aims to produce a computerized medical record storage system at Jampang Kulon General Hospital, the software system used is the waterfall development method, the type of research used is descriptive research with a qualitative approach. Collecting data by observation, and interviews. The storage system used at the Jampang Kulon General Hospital is a medical record number sorted by the final number (terminal digit filling system) and a centralized medical record document storage system. From this study found several problems in the management of medical record storage, including; (1) There is no recording in the form of medical record storage reports (2) Often the data that has been inputted is absent or inaccurate and data duplication often occurs (3) There are several medical record storage officers who have never attended training and are not medical record graduates . The solutions provided include; (1) Creating an information system that is easy to operate so that medical record officers can easily make reports on medical record storage (2) Officers must be given an understanding of medical record processing and given training in operating a computerized medical record storage system. The results of this study are to produce a computerized medical record storage system in order to assist medical record officers and to improve the hospital management information system for the better.